Restauration de la connectivité écologique : proposition méthodologique pour une localisation optimisée des passages à faune - Xavier Girardet; Jean-Christophe Foltête; Céline Clauzel; Gilles Vuidel (VertigO, 2016)
The development of linear infrastructures contributes to landscape fragmentation and directly impacts connectivity at regional scale. Consequently, the development of new methods to mitigate the impact of existing or planned infrastructure has become a major concern for the preservation of biodiversity. Among the existing methods, those based on graph theory offer interesting perspectives for regional planning and landscape management. The proposed protocol, based on modeling of the ecological network of a species or group of species, provides a methodological framework for decision support to mitigate the barrier effect of linear transport infrastructure. The results help to guide planners in finding a better compromise between ecological constraints (reach a maximum gain of connectivity) and economic constraints (limiting the number of crossing structures).